Resistensi dan Ambivalensi dalam Novel Al-Yaum Al-Maw’ud Karya Najib Kailani: Analisis Potkolonial - Hasanah, Ira Nur (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2021)
This paper focuses on the material object of a modern Egyptian novel entitled al-Yaum al-Maw'ud by Najib al-Kylani. This novel tells the story of the struggle of the Egyptian people under the leadership of King Najmuddin Ayun against the French Crusaders led by Prince Louis. What's interesting about this novel is that there are varied resistances carried out by various groups, as well as the very strong ambivalence attitude practiced by colonial figures. Meanwhile, the formal object is postcolonial theory using the deconstruction method. This theory is based on Edward Said's claim in his work